Length of Stay and Inpatient Costs Under Medicaid Managed Care in Florida - Jungwon Park PhD (SAGE Publishing, 2015)
This study examines the patterns of length of stay (LOS) and inpatient costs for both Medicaid managed care and nonmanaged care patients using data from Medicaid patients aged 18 to 64 years who were discharged from hospitals in Florida between 2006 and 2012. This study used pooled cross-sectional multilevel modeling. The results show that the type of Medicaid program in which patients were enrolled was significantly related to the hospital LOS and inpatient costs. Medicaid managed care patients had 7% shorter LOSs and a 1.9% lower inpatient cost than did Medicaid fee-for-service (FFS) patients. Medicaid managed care patients had shorter LOSs in the Medicaid managed care market with high competition. High managed care penetration generates a cost-decreasing spillover to Medicaid FFS patients.